If it's not what You are looking for type in the equation solver your own equation and let us solve it.
.1(x+111)=-2(3-x)
We move all terms to the left:
.1(x+111)-(-2(3-x))=0
We add all the numbers together, and all the variables
.1(x+111)-(-2(-1x+3))=0
We multiply parentheses
0.1x-(-2(-1x+3))+11.1=0
We calculate terms in parentheses: -(-2(-1x+3)), so:We get rid of parentheses
-2(-1x+3)
We multiply parentheses
2x-6
Back to the equation:
-(2x-6)
0.1x-2x+6+11.1=0
We add all the numbers together, and all the variables
-1.9x+17.1=0
We move all terms containing x to the left, all other terms to the right
-1.9x=-17.1
x=-17.1/-1.9
x=9+3.5527136788005E-15/1.9
| y/3+y/6=5/3 | | 180=6x+4 | | 28+102+7x+16=180 | | 18=-2(x-2)+4x | | 28+x=2 | | 18x-3.8x=7.36x-1.9x | | 7x=24+3x= | | 9x-25+6x=6x+3x+10+7 | | 6(x-4)+3=-21 | | 3/8x=2=14 | | -4w+3{2w-1}=17 | | 8m+20=400 | | 9a-11=28 | | X-92=7(2x+3)-9 | | 3(4q+1)=-21 | | 71-y=284 | | 3x+22+5x-13+4x+24=180 | | 8m+20=440 | | 3(2m-4)/6+5=8 | | -2(4x-4)-3x+5=-90 | | 2x+25=3x-21 | | 241=72-x | | -3(x+2)+15=14-4x | | (-x)+(-3)=-13 | | -10x+(-15)x+16=17+15 | | 11-n=-20 | | 2(3x-2)+5=-6(4-x)+25 | | 4x=-84x=−8 | | -4b+6=9b-7 | | 6(p-2)=56 | | -3x+11=9 | | 27=9−3x |